THE INFLUENCE OF GENDER AND FAMILY BACKGROUND ON FINANCIAL BEHAVIOR WITH FINANCIAL LITERACY AS A MEDIATION VARIABLE: STUDY ON GENERATION Z TEENS IN JAYAPURA CITY - Manalu, Palti; Ahlia, Isma Shalihi; Agustin, Sheilla Putri (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2024)
This study examines the determinants of financial behavior among Generation Z in Jayapura, Papua, with a specific focus on gender and family background influences, mediated by financial literacy. Using path analysis, the research surveyed 223 respondents aged 17-25 years through accidental sampling. The findings reveal that financial literacy directly influences Generation Z's financial behavior, with a significance value of 0.003 (p < 0.05). Both gender and family background significantly affect financial literacy, contributing 13.1% to its variance. The study demonstrates that gender indirectly influences financial behavior through financial literacy, with indirect effects (0.01312) exceeding direct effects (-0.153). However, family background shows stronger direct effects (0.425) compared to indirect effects (0.0276) on financial behavior, indicating that financial literacy does not effectively mediate this relationship. The overall model explains 24.7% of the variance in financial behavior. These findings contribute to understanding the complex relationships between demographic factors, financial literacy, and financial behavior among Generation Z in eastern Indonesia's context. The study recommends future research to incorporate additional variables to enhance the model's explanatory power and employ more precise measurement techniques.